Micro-Miniature Reed Switch Solution for Low Power Clinical Applications - Lockett, Albert; Wilson, Adam; Keys, Josh; Losier, Yves (CMBES Proceedings, 2012)
Improving the ease of configuring low power embedded microcontroller-based devices used within clinical rehabilitation settings and prosthetic limb systems can be a challenging problem for engineers and clinicians. This problem arises, in part, due to the fact that the desired product designs often tend to be in a small compact sealed form. As a result, gaining access to the system is difficult and time consuming. The work presented in this paper aims at overcoming this problem by developing a solution that uses a series of micro-miniature reed switches in conjunction with small magnets to configure different modules of the embedded devices without the need for disassembly and/or compromising the hermetic seal.